Intravenous and intracoronary fibrinolytic therapy in acute myocardial infarction: overview of results on mortality, reinfarction and side-effects from 33 randomized controlled trials. - Yusuf, S; Collins, R; Peto, R; Furberg, C; Stampfer, M; Goldhaber, S; Hennekens, C (1985)
During the past 25 years, 24 randomized trials of intravenous (IV) fibrinolytic treatment have been reported, involving a total of some 6000 patients in the acute phase of myocardial infarction. Most tested IV streptokinase (SK), but a few tested IV urokinase (UK). In the past 2 or 3 years numerous small randomized trials of intracoronary (IC) SK have been started, 9 of which, involving a total of about 1000 such patients, have been reported. Because all of these IV and IC trials were small (the largest including only 747 patients), their separate results appear contradictory and unreliable. But, an overview of the data from these trials indicates that IV treatment produces a highly significant (22% +/- 5%, P less than 0.001) reduction in the odds of death, an even larger reduction in the odds of reinfarction, and an absolute frequency of serious adverse effects to set against this that is much smaller than the absolute mortality reduction. The apparent size of the mortality reduction in the IV trials was similar whether anticoagulants were compulsory or optional, whether treatment was in a coronary care unit or an ordinary ward and, surprisingly, whether treatment began early (less than 6 h from onset of symptoms) or late (generally 12-24 h). In addition, there was no evidence that UK was more effective than the less expensive SK, or that, despite their technical complexity, the new IC regimes were more effective than the old IV regimes. Even the IV schedules that have been studied in randomized trials were, however, quite complex, and the IC schedules were far more so. Perhaps partly because of this, none of them is widely used. If so, then some much simpler, and hence more widely practicable, IV SK regimes should be developed and tested. For example, a simple one hour high-dose IV SK infusion, without anticoagulation, will successfully convert virtually all of the available plasminogen into plasmin. But, it may be several years before the net effects on mortality of any more widely practicable IV SK regimes can be agreed unless many of the hospitals that do not wish routinely to use IC regimes or the complex previous IV regimes will collaborate in multicentre randomized trials that can, if necessary, continue rapid intake until some tens of thousands of patients have been randomized, and some thousands of deaths have been observed among the control and treated patients. The same, of course, may be true for any other fibrinolytic regimes (e.g. infusion of tissue plasminogen activator) if their net effects on mortality are comparable to those of IV SK.